2010
DOI: 10.1534/genetics.109.109934
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Euchromatic Chromosome Breaks by Efficient de novo Telomere Addition in Drosophila melanogaster

Abstract: Previously, we observed that heterochromatic 4 and Y chromosomes that had experienced breakage in the male germline were frequently transmitted to progeny. Their behavior suggested that they carried functional telomeres. Here we show that efficient healing by de novo telomere addition is not unique to heterochromatic breaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…For instance, if chromosome healing was very inefficient except at a few sites, it might account for these results. However, previous results show that healing can occur at many sites in heterochromatin and euchromatin (Mason et al 1984;Levis 1989;Biessmann et al 1990;Tower et al 1993;Ahmad and Golic 1998;Mikhailovsky et al 1999;Titen and Golic 2010;Beaucher et al 2012;Titen et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, if chromosome healing was very inefficient except at a few sites, it might account for these results. However, previous results show that healing can occur at many sites in heterochromatin and euchromatin (Mason et al 1984;Levis 1989;Biessmann et al 1990;Tower et al 1993;Ahmad and Golic 1998;Mikhailovsky et al 1999;Titen and Golic 2010;Beaucher et al 2012;Titen et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These events include mobilization of P elements inserted near the telomere (Tower et al, 1993), breakage of dicentric chromosomes during anaphase (Ahmad and Golic, 1998; Titen and Golic, 2010), and induction of an enzymatic cut in a P element construct inserted in the telomere region (Gao et al, 2010; Beaucher et al, 2012). A recent analysis of de novo telomere formation at double strand breaks (DSBs) generated by the enzymatic cut method showed that neotelomere formation occurs rather frequently in wild type males and is facilitated by partial disruption of DNA repair functions such as those of Mu2/MDC1, Rad51, ATRIP, Nbs, or ATM (Beaucher et al, 2012).…”
Section: Drosophila Telomeres Are Epigenetically Determined Structuresmentioning
confidence: 99%
“…TDs with neotelomeres have also been recovered from mutational events occurred in the male germline. These events include X-ray induced breaks in the Dp(1;f)1187 mini-chromosome, 16 the mobilization of a P element located near the telomere, 17 breakage of dicentric chromosomes generated by site specific recombination, 18,19 and induction of an enzymatic cut in an I-Sce1 site placed within a P element construct inserted near the telomere. 20 Collectively, these results demonstrate that the HTT elements are not required for fly telomere assembly and that virtually any DNA sequence has the ability to form the nucleoprotein complex that protects the ends of Drosophila chromosomes.…”
Section: Termininmentioning
confidence: 99%
“…[22][23][24][25] Human telomeres terminate with a single stranded overhang of tandem TTAGGG repeats, which loops back invading the to the extremities of various types of terminally deleted chromosomes demonstrating that these proteins bind chromosome ends independently of the sequence of terminal DNA. 19,20,33,34 It should be noted that despite its direct interaction with HOAP, HipHop and Moi, HP1 should not be considered as a terminin component, because it does not localize exclusively at telomeres and has multiple telomere-unrelated functions (reviewed in refs. 46 and 47).…”
Section: Telomere Capping Complexes In Organisms With Telomerasementioning
confidence: 99%